THE APPLICABILITY OF THE CRYSTAL STRUCTURE OF TERMOTOGA MARITIMA 4-α-GLUCANOTRANSFERASE AS THE TEMPLATE FOR SULOCHRIN AS α-GLUCOSIDASE INHIBITORS - Rizna Triana Dewi; Yulia Anita; Enade Perdana Istyastono; Akhmad Darmawan; Muhamad Hanafi (Indonesian Journal of Chemistry, 2009)
Interaction of sulochrin to active site of glucosidase enzyme of Termotoga maritime has been studied by employing docking method using Molecular Operating Environment (MOE), in comparison with those are reports of established inhibitor α-glucosidase such as acarbose, miglitol and voglibose, and salicinol, as reference compounds. The crystal structure T. maritima α-glucanotransferase (PDB code: 1LWJ) can be employed to serve as the template in the virtual screening of S. cerevisiae α-glucosidase. The comparison between the binding pocket residues of Thermotoga maritima α-glucanotransferase and Saccharomyces cerevisiae α-glucosidase show a high sequence identity and similarity. The result showed that sulochrin could be located in the binding pocket and formed some interactions with the binding residues. The ligands showed proper predicted binding energy (-6.74 - -4.13 kcal/mol) and predicted Ki values (0.011 - 0.939 mM). Sulochrin has a possibility to serve as a lead compound in the development of new α-glucosidase inhibitor.